Association between Triglyceride-Glucose (TyG) Index and Severity of Coronary Artery Disease Assessed by SYNTAX Score (University Heart Journal, 2025)
Background:Trigyceride-glucose (TyG) index is a composite indicator composed of triglyceride (TG) and fasting blood glucose (FBS). It is a simple, reliable and easily accessible marker of insulin resistance (IR) which is associated with different metabolic and cardiovascular diseases (CVD) including coronary artery disease (CAD).Objective: To investigate the correlation between the TyG index and cardiovascular risk factors, and the predictive value of TyG index with severity of CAD assessed by SYNTAX score.Methods: This cross-sectional analytical study was done in the Department of Cardiology, Bangladesh Medical University, Dhaka, Bangladesh, from January 2025 to June 2025 including a total of 50 patients undergoing coronary angiogram (CAG) during the index hospitalization. The TyG index was calculated as Ln [fasting triglyceride (mg/dL) ×fasting glucose (mg/dL)]/2. Linear regression analysis were done to assess relationship between cardiovascular risk factors and TyG index. The severity of CAD was assessed by the SYNTAX score and logistic regression analysis was done to assess predictive value of TyG index with severity of CAD.Results: On the basis of median TyG index level level (9.33) study population were divided into two groups (low TyG index and high TyG index). In univariate linear regression analysis showed positive relation of TyG index with male gender (p=0.039), diabetes mellitus (p